Pengaruh Perencanaan Pajak, Profitabilitas, Ukuran Perusahaan dan Leverage Terhadap Nilai Perusahaan pada Perusahaan Pertambangan yang Terdaftar di BEI Periode 2020-2022 - Adetia Apika; Eko Prasetyo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In building a company, each company will maximise its performance to achieve its goals. Because each company has a goal to obtain profit or profit from the production activities carried out and to increase the value of the company. The purpose of this study was to determine the effect of tax planning, profitability, company size and leverage on firm value. This research was conducted on the Indonesia Stock Exchange (IDX) taking data through the website www.idx.co.id to obtain annual report data that has been published and audited by the company in the 2020-2022 period. While the research time was conducted in 2024, the observation period carried out by researchers was in the order of time from 2020 to 2022. The type of approach in this study is to use a quantitative approach. With this type of research relationship using associative methodology where this method is used to determine the interaction or impact between several variables. The results of this study indicate that tax planning has a significant positive effect on firm value The results of this study indicate that profitability has a significant positive effect on firm value The results of this study indicate that company size has no significant effect on firm value. The results of this study indicate that leverage has a significant positive effect on firm value.